Multicultural Spanish dictionary : how everyday Spanish differs from country to country - Martinez, Augustin (Taylor Trade, 2011)
An updated and revised edition of the widely used first edition. Includes hundreds of new technology terms and entries from even more Spanish-speaking countries.